2020
DOI: 10.1155/2020/7452697
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Conflict among Iranian Emergency Medical Technicians and Its Relationship with Time Management Skills: A Descriptive Study

Abstract: Background. Work-Family Conflict (WFC) is a form of interrole conflict in which an active participation in occupational activities causes strain and interferes with family roles of workers and vice versa. It is a major source of occupational stress among workers and personnel. Emergency Medical Technicians (EMTs) are an important part of the healthcare system that respond to emergencies. The EMTs experience high level of job stress, which may affect their ability to perform their family roles, and, on the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…Study findings showed that EMS staff experienced different levels of stress due to personal and professional conflicts such as long shifts and work-family problems. In line with this finding, a former study showed that EMS providers and their family members suffered from stress due to work-family conflicts [43]. Another source of occupational stress in the present study was interpersonal conflicts among EMS colleagues and ineffective interpersonal interactions with rescue, relief, and hospital staff.…”
Section: Personal and Professional Conflictssupporting
confidence: 88%
“…Study findings showed that EMS staff experienced different levels of stress due to personal and professional conflicts such as long shifts and work-family problems. In line with this finding, a former study showed that EMS providers and their family members suffered from stress due to work-family conflicts [43]. Another source of occupational stress in the present study was interpersonal conflicts among EMS colleagues and ineffective interpersonal interactions with rescue, relief, and hospital staff.…”
Section: Personal and Professional Conflictssupporting
confidence: 88%
“…The results is empirically confirmed by Goudarzi, Sheikhi, and Kheir, (2012) study which showed that time-management was negatively influence on work-family conflict among Iran employees. These findings shared consistent result with other study by Beyramijam, Shahrestanaki, Khankeh, Aminizadeh, Dehghani, and Hossein (2020), that shows an inverse and significant correlation between time-management and work-family conflict experienced by employees. Green and Skinner (2005) explain that individual requires straightening their capability to organize time successfully to accomplish a sufficient balance of work and family.…”
Section: B Time-managementsupporting
confidence: 93%
“…Moreover, a high frequency of night shifts also led to increased workload (33), and irregular working time might lead to sleep disorders simultaneously (28,40), thereby possibly had an impact on private life. Accordingly, it is necessary to ensure adequate emergency nurses (3) and reasonably adjust working time and night shift frequency (10,41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in many countries confirmed that the prevalence of WFC among nurses was high and mainly at a high level (4)(5)(6)(7). As a consequence of the fast work pace, high pressure, and frequent violence in the emergency department (8,9), the WFC of emergency nurses is more severe than that of nurses in other departments (10).…”
Section: Introductionmentioning
confidence: 99%